Science and faith dialoguing in life science courses - Erichsen, Ronaldo; Jardim, Berenice Soares Bueno (Vox Scripturae - Revista Teológica Internacional, 2018)
The article reports the actions developed through a proposed project in the São Gabriel campus of UNIPAMPA, whose objective in the academic community was to raise, along with students who had religious convictions, the points of interrelationship between religion and science that affected them. From this initial survey, to propose to these students current knowledge of Christian apology, to enable them to elaborate a convergent dialogue between the two points of view, and to serve as an instrument for dialogue with the other members of the academic world, as well as outside of it.